Renaturation urbaine : enjeux de biodiversité d’une métropole réémergente - Nguyen Thuy An Pham (Projets de Paysage)
Historically, Ho Chi Minh City is a city of plants and water marked by the presence of lush vegetation and a hydraulic system which harbours a variety of aquatic ecosystems. Thirty years after the policy of Renovation was launched (1986), it has changed into a modern city faced with accelerated urbanisation. Natural and agricultural spaces are being covered in concrete, green spaces are being greatly reduced, and lakes and waterways are being filled in or polluted. The question of biodiversity within the urban fabric of Ho Chi Minh City has become a central issue for urban planners and stakeholders. The article seeks to shed light on the measures taken in urban renaturing at project and town planning levels. Can such a process contribute to preserving and restoring the biodiversity of the city ?